Efficient P2O5 Catalyzed Microwave Assisted One Pot Synthesis of Substituted Dihydropyrimidine-2(1H)-ones - NAZERUDDIN*, G.M.; PANDHARPATTE, M.S. (Asian Journal of Chemistry, 2009)
Phosphorus pentaoxide catalyzed and microwave enhanced three component Biginelli reaction of aldehyde, 1,3-dicarbonyl compounds and urea or thiourea under reflux microwave conditions to afford dihydropyrimidin-2-(1H)-ones in excellent yield is described. The improved procedure is fairly simple, facile and environment friendly.